2001
DOI: 10.19182/remvt.9778
|View full text |Cite
|
Sign up to set email alerts
|

Efficacité antiparasitaire de la poudre de graines de papaye (<em>Carica papaya</em>) sur les strongles gastro-intestinaux des moutons Djallonké au sud du Bénin

Abstract: L’efficacité antiparasitaire des graines de papaye (Carica papaya) a été testée sur les strongles gastro-intestinaux. L’étude a porté sur 80 moutons répartis en cinq lots de 16 animaux (dix brebis et six agneaux) : un lot témoin, un lot témoin traité avec de l’albendazole à la dose de 5 mg/kg et trois lots ayant reçu de la poudre de graines de papaye séchées au soleil ou à l’étuve à des doses de 100, 200 ou 400 mg/kg de poids vif. Les taux d’infestation par les strongles gastrointestinaux des ovins ont varié e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…In a similar study, the seeds aqueous extract of Annona senegalensis inhibited 11.5% egg hatching at 7.1 mg mL −1 against H. contortus (Alawa et al 2003). The in vivo study of gastrointestinal nematode-infected sheep, the papaya seed extracts induced 80% of egg hatching reduction on H. contortus (Hounzangbe-Adote et al 2001). The present study revealed that the leaves and seeds extracts of M. azedarach showed good results for the inhibition of egg hatching and larval development of H. contortus.…”
Section: Resultsmentioning
confidence: 79%
“…In a similar study, the seeds aqueous extract of Annona senegalensis inhibited 11.5% egg hatching at 7.1 mg mL −1 against H. contortus (Alawa et al 2003). The in vivo study of gastrointestinal nematode-infected sheep, the papaya seed extracts induced 80% of egg hatching reduction on H. contortus (Hounzangbe-Adote et al 2001). The present study revealed that the leaves and seeds extracts of M. azedarach showed good results for the inhibition of egg hatching and larval development of H. contortus.…”
Section: Resultsmentioning
confidence: 79%
“…Some authors have described the ovicidal activity of various herbal plants against Haemonchus contortus. In an in vivo study of gastrointestinal nematode-infected sheep, the papaya seed extracts induced 80 % of egg hatching reduction on H. contortus (Hounzangbe-Adote et al 2001). Costa et al (2002) have reported that the seed ethanol extract of Mangifera indica revealed 91 % effective inhibition of egg hatching at 10 mg/mL on H. contortus.…”
Section: Discussionmentioning
confidence: 99%
“…The ovicidal activity of herbal plants against many insect species Tunc et al 2000) and also Haemonchus contortus (Hounzangbe-Adote et al 2001;Costa et al 2002;Kamaraj and Rahuman 2011) have been previously evaluated.…”
Section: Discussionmentioning
confidence: 99%